Improvement of English Skills Youth Organization Penrang Village on Wajo Regency - Satriani; Amiruddin; Inayah, Nur; Kafrawi, Muhammad; Hikmah, Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
This community service program is based on the importance of soft skills for the younger generation. The current initiative aims to stimulate highlanders' interest in learning English through environmental and natural folklore literature, as well as to improve soft skills for Karang Taruna in Penrang Village, Wajo. The goal is to pique people's interest in learning English and help them improve their skills (soft skills). To discover knowledge and support technology, the program use question and answer and discussion methods. During the learning process, the lecturing method was employed to obtain a theoretical understanding of English. Youth are more likely to understand English when it is taught through natural-themed storybooks, according to the findings. Youths exhibit significant improvement after using the book. Another benefit was that young adults may acquire English quickly and use it as a springboard for other activities.